Behavioral economics and the impact of message framing on financial planning intentions - Todd, Timothy Michael Jr (Kansas State University, 2019)
Neoclassical economics asserts that individuals maximize their utility subject to constraints, such as income. Rational choice and expected utility theories are natural outgrowths of utility maximization and posit that, when making decisions, individuals consider all information, weigh the costs and benefits, and then consistently make the best choice to maximize their utility. Behavioral economics, on the other hand, advances that these constant-rationality assumptions are dubious and unrealistic. Among other things, behavioral economics recognizes that individuals use heuristics and that decision making can be subject to cognitive biases, which cause divergences from neoclassical rational choice expectations. A popular (and growing) use of applied behavioral economics is in “choice architecture” and “nudges”—that is, increasing desirable outcomes by strategically structuring information and choices (i.e., the framing of information and choices). In financial planning, there are many financially healthy behaviors, such as planning for retirement, engaging in monthly budgeting, and ensuring that various risks are covered by insurance. Despite these tasks being objectively useful, positive, and valuable behaviors, many individuals do not engage in these behaviors (or other behaviors that are regularly recommended by financial advisors and planners). Therefore, this dissertation investigated whether applying a behavioral economics-based approach—namely narrative message framing through a prospect theory lens—affected the intentions to engage in retirement planning, monthly budgeting, and analyzing the need for insurance. In short, whether narrative message framing can be used as a “nudge” to increase financial planning intentions. This study also incorporated regulatory focus theory, which regards how individuals self-regulate. Under this theory, framing effects may be stronger when the frame matches the individual’s regulatory focus—this is known as regulatory fit. Using primary data from randomized experiments, this dissertation explored three financial planning domains and investigated four research questions in each domain: (a) the effect of narratives on financial-planning intentions; (b) whether the valence of the narrative (positive or negative framing in the story) mattered (and if this varied by domain); (c) whether the framing effect, if any, depended on the individual-level characteristic of regulatory focus; and (d) whether regulatory fit enhanced framing effects. The three financial planning domains explored were retirement planning (a behavior with future consequences), cash-flow and budget planning (a behavior with present consequences), and insurance-needs planning (a behavior that involved risk analysis). Results indicated that narrative message framing was effective to increase financial planning intentions. Moreover, the framing effect depended on the underlying financial behavior. The framing effect also varied based on the individual’s regulatory focus. Stated simply, stories were powerful, framing mattered, and people responded differently to those frames. These findings are relevant to financial planners, financial services companies, financial-related non-profits and professional organizations, and policymakers, among others, all of whom can use these results to increase (nudge) the intentions to engage in various positive financial behaviors.
Keywords: Financial planning; Behavioral intentions; Behavioral economics